JOURNALISTIC CENSORSHIP DURING COVID-19 BY USING THE EGYPTIAN COMMUNICABLE DISEASES LAW - Sabry AlAshry, Miral (Brazilian journalism research, 2022)
ABSTRACT – This study investigated the effectiveness of the Egyptian Law on Communicable Diseases No. Law 152 of 2021, which sought to regulate procedures and measures necessary to fight the spread of epidemics and pandemics, as well as its implications for journalistic practice and press freedom in Egypt. The study was underpinned by the “Theory of State Censorship”. The study used in-depth interviews, which were done with 30 Egyptian journalists. The finding of the study indicated that the government placed restrictions on journalists by using Law 152 of 2021 to control the news relating to pandemics. The reason was to allow the government to exercise greater information control through digital policy. RESUMO – Este estudo investigou a eficácia da Lei Egípcia de Doenças Transmissíveis – Lei 152 de 2021 –, que buscou regular procedimentos e medidas necessárias para combater a propagação de epidemias e pandemias, bem como suas implicações para a prática jornalística e a liberdade de imprensa no Egito. O estudo foi sustentado pela “Teoria da Censura do Estado”. O estudo utilizou entrevistas em profundidade, que foram feitas com 30 jornalistas egípcios. Os resultados do estudo indicam que o governo impôs restrições aos jornalistas usando a Lei 152 de 2021 para controlar as notícias relacionadas à pandemia. O motivo era permitir que o governo exercesse maior controle das informações por meio da política digital. RESUMEN – Este estudio investigó la efectividad de la Ley Egipcia sobre Enfermedades Transmisibles – Ley 152 de 2021 –, que busca regular los procedimientos y medidas necesarias para combatir la propagación de epidemias y pandemias, así como sus implicaciones para la práctica periodística y la libertad de prensa en Egipto. El estudio se basó en la “Teoría de la Censura del Estado”. El estudio utilizó entrevistas en profundidad, que se realizaron con 30 periodistas egipcios. El hallazgo del estudio indicó que el gobierno impuso restricciones a las restricciones al usar la Ley 152 de 2021 para controlar las noticias relacionadas con pandemias. La razón fue permitir que el gobierno ejerciera un mayor control de la información a través de la política digital.